Flexible and Transparent Luminescent Cellulose-Transition Metal Cluster Composites - Maria Amela-Cortes; Noée Dumait; Franck Artzner; Stéphane Cordier; Yann Molard (Nanomaterials, 2023)
Red-NIR luminescent polymers are principally obtained from petroleum-based derivatives in which emitters, usually a critical raw material such as rare-earth or platinum group metal ions, are embedded. Considering the strong ecological impact of their synthesis and the major risk of fossil fuel energy shortage, there is an urgent need to find alternatives. We describe a luminescent nanocomposite based on red-NIR phosphorescent molybdenum nanoclusters, namely Cs2Mo6I8(OCOC2F5)6, embedded in an eco-friendly cellulose biopolymer matrix that is obtained by a simple solvent casting technique. While homogeneity is kept up to 20 wt% of cluster complex doping, annealing hybrids leads to a large increase of their emission efficiency, as demonstrated by quantum yield measurements.